ANALISIS YURIDIS TUGAS DAN WEWENANG BADAN KEHORMATAN DEWAN PERWAKILAN RAKYAT DAERAH DALAM MENGAWASI KODE ETIK - Abdul Hijar Anwar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The Honorary Body is an instrument of the DPRD established to uphold the DPRD code of ethics. Basically, the Honorary Body is an internal oversight body of the DPRD. There are 2 (two) honorary body functions, which are active functions and passive functions. The active function of the Honorary Agency is the supervisory function in which the Honorary Agency evaluates absences, legal products produced by the DPRD, and intensity of meetings conducted by board members. The passive function of the Honorary Agency is the BK action to follow up when there are complaints of indications of violations by members of the board. The Board of Honor always appeals to council members not to commit violations or deviations.